Hydrogenases and the Role of Molecular Hydrogen in Plants - Russell, Grace (Plants (Basel), 2020)
Molecular hydrogen (H(2)) has been suggested to be a beneficial treatment for a range of species, from humans to plants. Hydrogenases catalyze the reversible oxidation of H(2), and are found in many organisms, including plants. One of the cellular effects of H(2) is the selective removal of reactive oxygen species (ROS) and reactive nitrogen species (RNS), specifically hydroxyl radicals and peroxynitrite. Therefore, the function of hydrogenases and the action of H(2) needs to be reviewed in the context of the signalling roles of a range of redox active compounds. Enzymes can be controlled by the covalent modification of thiol groups, and although motifs targeted by nitric oxide (NO) can be predicted in hydrogenases sequences it is likely that the metal prosthetic groups are the target of inhibition. Here, a selection of hydrogenases, and the possibility of their control by molecules involved in redox signalling are investigated using a bioinformatics approach. Methods of treating plants with H(2) along with the role of H(2) in plants is also briefly reviewed. It is clear that studies report significant effects of H(2) on plants, improving growth and stress responses, and therefore future work needs to focus on the molecular mechanisms involved.